Analisis Peramalan Permintaan pada Part Arm Rear Brake KWBF di PT Ciptaunggul Karya Abadi - Zaskya Indah Vindari; Wahyudin Wahyudin; Adinda Gita Azzahra; Samitha Pujia Khan; Sekar Mustika Ayuningtyas; Wagiana Rohmah (Jurnal Serambi Engineering, 2023)
In production activities, fulfillment customer demand requires a method of calculating uncertainty the demand prediction in the future period. PT Ciptaunggul Karya Abadi has its own forecasting system, but the results are different from the actual data. One of the productions is Arm Rear Brake KWBF part shows a ± stock difference from actual demand data with forecasting data each month. This study to propose improvements to the forecasting system for Arm Rear Brake KWBF part by comparing three forecasting systems and selecting the lowest error rate. The method used in solving these problems is a results comparison of the moving average method, trend analysis method and company forecasting system with data collection techniques through observation and interview. The data used is in the form of general data such as company identity and special data such as historical production data of the company. The results of this study indicate that the lowest error is found in trend analysis method with MAD of 1811, MSE of 5702679 and MAPE of 0.46. So, the trend analysis method on the Arm Rear Brake KWBF part is feasible to be applied in the company.